1963
DOI: 10.1063/1.1734303
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of CH4 and CD4. Interpretation of the Properties of the Solids

Abstract: The paper gives the results of calorimetric measurements of the heat capacities of solid and liquid CH4 and CD4, the heats of fusion of both substances and the heat of vaporization of CD4. The results for the solids, which extend from 2.3°K to the triple points, are analyzed in some detail. In order to account for the apparent zero-point entropies of both CH4 and CD4 quantitatively, it is necessary to recognize the existence of different nuclear spin species (as with ortho and para hydrogen) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(39 citation statements)
references
References 53 publications
1
37
1
Order By: Relevance
“…Our conversion measurements are in good agreement with results published earlier for CH 4 samples (see Fig. 4) [4][5][6][7][8][9][10][11][12][13][14][15][16]. The CD 4 results we have obtained for the first time.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our conversion measurements are in good agreement with results published earlier for CH 4 samples (see Fig. 4) [4][5][6][7][8][9][10][11][12][13][14][15][16]. The CD 4 results we have obtained for the first time.…”
Section: Resultssupporting
confidence: 92%
“…Several experiments have shown that this conversion occurs between nuclear spin symmetry species in solid methane (CH 4 ) [4][5][6][7][8][9][10][11][12][13][14][15]. At the same time, there are few reports where the conversion in solid deuterated methane (CD 4 ) was observed [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Results presented here are in good agreement with the publications cited above and can also be interesting and useful from the point of astrophysics. The purpose of our research was a more detailed study of temperature dependence of the refractive index and density of cryofilms solid methane, for which, as noted earlier [2][3][4][5], at T = 20.4 K the transition from the orientational disordered phase (α-phase) to the partially ordered phase (β-phase) occurs. It is assumed that this transition must influence the refractive indices of solid methane.…”
Section: Discussionmentioning
confidence: 98%
“…The starting point of this long history of research was the discovery by Clusius (1929) [1] of the anomalous behavior of the heat capacity of methane at temperature T = 20.4 K. In 1959 James and Keenan [2] demonstrated theoretically that this anomaly may be explained as the phase transition from the high-temperature orientationally disordered phase of methane (α-phase) to the partially ordered phase at a temperature below T c = 20.4 K (β-phase). Later it was discovered [3][4][5] that the β-phase is the intermediate state of solid methane towards the full orientation ordering phase (γ-phase).…”
Section: Introductionmentioning
confidence: 99%
“…Phase transitions in this temperature range are reported in the literature for solid CH. and solid 0, [48,49], and other solidified gases exhibit similar transitions from one crystalline structure to another at other temperatures.…”
Section: Aedc-tr-70-123mentioning
confidence: 89%